Hybridization of Genetic Algorithm with Homotopy Analysis Method for Solving Fractional Partial Differential Equations - Ahmed Entesar; Omar Saber; Waleed Al-Hayani (Eurasian Journal of Science and Engineering, 2018)
In this work, the Homotopy Analysis Method (HAM) is applied to solve fractional Partial Differential Equations (PDEs). The solution of HAM has improved the results by using Genetic Algorithm (GA). The hybrid method (proposed) is applied for types of problems where analytical solutions approximate are obtained. Numerical experiments are also presented.